PENGEMBANGAN SISTEM MANAJEMEN TEMA WEBSITE BERBASIS METODE AGILE SCRUM - Wahyudi Chrisdianto; Sukmawati Anggraeni Putri (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2022)
The Psychological test conducted by Pilih Jurusan is to create students who understand themselves and their characteristics so that they can help realize Indonesia's great ambition of “Indonesia Emas 2045”. for that, we need a platform that can be accessed anywhere and anytime, but in its development phase there are many obstacles, especially in the application development process, so the idea was formed to develop a theme management system, developed with webpack, NodeJS, PostCSS, TailwindCSS, Javascript, AlpineJS, and PHP 7.4 Based on Codeigniter 3 Framework. The development method is using Agile Scrum with research which is based on observations, interviews, and literature studies. The result is a Theme Management System, which is not integrated directly into the main app so that it can be used in other projects, whose implementation in this psychological test application has an impact on increasing user experience, efficiency development time, and resources, as well improving the performance of the aplication when used.